Telling the Christmas story in words and music: the development of and contemporary missional value of the Festival of Nine Lessons and Carols within cathedrals - Robinson, Andrew (Journal of beliefs and values, 2023)
This study investigates the development of the Festival of Nine Lessons and Carols, considers how in this context the Christmas story is told in word and music, and examines how this service contributes to the Church’s mission of proclaiming the story of faith today. It focuses on the initial development of the service in Truro 1880, its subsequent adaptation at King’s College, Cambridge, and how the tradition is reflected in and developed throughout the twentieth and twenty-first century, using examples from four Cathedrals in England: Coventry, Salisbury, Durham, and Truro. This paper shows how, with adaption and careful planning, this service can continue to be used as a missional tool to tell the story of faith in the twenty-first century.